(untitled) (Health Renaissance, 2011)
Background: Although breastfeeding is a common practice in Nepal, proper breastfeeding is on the decline due to several factors. The impact of knowledge about breastfeeding practice, i.e., duration of breastfeeding, proper techniques, proper time of weaning is poorly understood. Objective: To assess the knowledge and actual practices of mothers regarding breastfeeding. Methods: Cross sectional study was carried out on 200 mothers of under 1 year old children who attending the pediatric Out Patient Department, well baby clinic and immunization clinic at BPKIHS, Dharan. Mothers were interviewed using pre-designed questionnaire. Result: All mothers knew that they had to breast feed their babies, but they did not have adequate knowledge about the appropriate way of breastfeeding. 10% knew that they have to initiate breast feeding within ½ hour of birth, 10% had idea on prelacteal feed, 25% had idea on importance of colostrums, 15% knew the meaning of exclusive breast feeding, and 15% of the mothers had idea on importance of night feeding. 41.5% mothers initiated breast feeding within ½ hour of birth, 33% mothers gave prelacteal feed, colostrum was fed by 95%, 15% were practicing exclusive breast feeding, 90% mothers were practicing night feeds, 15% mothers practiced feeding one side at a time, 60% mothers were practicing inappropriate attachment and positioning, None of the mothers got any advice regarding breast feeding during ANC visits. Conclusion: Undesirable cultural practices such as giving prelacteal feeds, late initiation of breastfeeding after birth, delay in introduction of weaning foods and avoiding exclusive breastfeeding are still prevalent among the mothers. The maternal knowledge towards breast feeding was inadequate and there was a big gap between actual and desired practices. Keywords: breast feeding; colostrums; weaning DOI: http://dx.doi.org/10.3126/hren.v9i3.5590 HR 2011; 9(3): 194-200